Lithium supplement agent and preparation method thereof, positive plate and lithium ion battery

By coating carbon nanotubes and silicon carbide on the surface of lithium-rich lithium ferrate, the problems of severe gas production side reactions, high surface residual alkali content and poor air stability in traditional lithium supplements are solved under high pressure, and the internal resistance of the battery is reduced , the effect of improving the electrolyte liquid absorption rate and improving the battery cell rate and circulation performance.

CN119481067APending Publication Date: 2025-02-18JIANGSU PYLON BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411819786.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional lithium-rich lithium ferrate supplements have severe gas production side effects under high pressure, high surface residual alkali content and poor air stability, which affect the electrochemical performance of the battery.

Method used

By coating carbon nanotubes and silicon carbide on the surface of lithium-rich lithium ferrate, a new lithium supplement agent was prepared to improve its air stability and reduce the amount of residual alkali on the surface.

Benefits of technology

This lithium supplement agent can reduce the internal resistance of the battery, increase the liquid absorption rate of the electrolyte, reduce the decomposition potential, reduce the side reaction of the battery cell, and improve the rate performance and circulation performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481067A_ABST
    Figure CN119481067A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplement agent and a preparation method thereof, a positive plate and a lithium ion battery, and relates to the technical field of batteries. The lithium supplement agent provided by the invention comprises lithium-rich lithium ferrite; the surface of the lithium-rich lithium ferrite is coated with carbon nanotubes and silicon carbide; the mass ratio of the carbon nano tube is 0.01%-0.5%; the mass ratio of the silicon carbide is 0.01%-1%. The lithium supplement agent can reduce the internal resistance of the battery, improve the liquid absorption rate of a battery positive pole piece to electrolyte, reduce the decomposition potential, reduce the side reaction of a battery cell, improve the rate capability and cycle performance of the battery cell, reduce the crushing of a lithium supplement agent core body, and avoid the side reaction of lithium supplement agent residues and the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium supplement and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] With the deepening of lithium-ion battery material research, the improvement of manufacturing level and the market's requirements for battery performance, the traditional idea of ​​replacing electrode materials and developing new electrolytes to improve lithium-ion battery performance has become very limited. The emergence of pre-lithiation technology has provided an effective solution for improving the performance of lithium-ion batteries, especially in improving irreversible capacity loss and increasing energy density, injecting new vitality into the development of lithium-ion battery technology. Now commercial attempts are being made to use lithium-rich lithium iron oxide as a lithium supplement.

[0003] However, traditional lithium-rich lithium ferrate lithium supplements have serious gas production side reactions under high pressure, high surface residual alkali content and poor air stability, which have adverse effects on the electrochemical performance of the battery. At present, different research institutions have used carbon coating to reduce contact with air, improve the air stability of lithium-rich lithium ferrate and reduce the amount of residual alkali on the surface. For example, CN110518298A discloses a Co-doped lithium ferrate lithium supplement, but the lithium ferrate synthesized by this method has an unstable interface and high residual alkali. Patent CN114050258A discloses a Li5Fe a M b O4 lithium supplement, wherein the element M is one or more of Ni, Co, Mn, and Cu. However, compared with conventional lithium ferrite, the adsorption of electrolyte is reduced after carbon coating, and it cannot fully infiltrate into the electrolyte.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a lithium supplement to solve the above technical problems.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned lithium supplement.

[0007] The third object of the present invention is to provide a positive electrode sheet.

[0008] A fourth object of the present invention is to provide a lithium ion battery.

[0009] In order to achieve the above objectives, the following technical solutions are adopted:

[0010] In a first aspect, the present invention provides a lithium supplement, including lithium-rich lithium ferrate;

[0011] The surface of the lithium-rich lithium ferrite is coated with carbon nanotubes and silicon carbide;

[0012] The mass proportion of the carbon nanotubes is 0.01%-0.5%;

[0013] The mass proportion of the silicon carbide is 0.01%-1%.

[0014] As a further technical solution, the chemical formula of the lithium-rich lithium iron oxide is: Li a Fe b O4;

[0015] Among them, 5.6≥a≥4.4, 1.2≥b≥0.8.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned lithium supplement, comprising the following steps:

[0017] A lithium source and an iron source are mixed, and a precursor powder is obtained after heating treatment, and then the precursor powder is mixed with a carbon source and a silicon source to obtain a mixed powder, and then the mixed powder is sintered to prepare the lithium supplement agent;

[0018] The carbon source includes carbon nanotubes.

[0019] As a further technical solution, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium oxide.

[0020] As a further technical solution, the iron source includes at least one of iron oxide, ferroferric oxide, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous citrate, ferrous sulfate or ferric hydroxide.

[0021] As a further technical solution, the carbon source also includes an inorganic carbon source and an organic carbon source;

[0022] The inorganic carbon source includes at least one of graphite, graphene, fullerene or carbon nanotube;

[0023] The organic carbon source includes at least one of glucose, sucrose, lignin urea, glycine or citric acid.

[0024] As a further technical solution, the silicon source includes silicon powder and silicon dioxide.

[0025] As a further technical solution, the sintering includes: in an inert atmosphere, keeping the mixed powder at 400-600° C. for 4-8 hours, and then keeping it at 800-1000° C. for 8-12 hours.

[0026] In a third aspect, the present invention provides a positive electrode sheet, wherein the slurry layer of the positive electrode sheet includes the above-mentioned lithium supplement agent.

[0027] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The lithium supplement agent provided by the present invention can reduce the internal resistance of the battery, increase the liquid absorption rate of the battery positive electrode plate to the electrolyte, reduce the decomposition potential of the lithium ferrite, reduce the side reactions of the battery cell, improve the rate performance and cycle performance of the battery cell, reduce the crushing of the lithium supplement agent core, and avoid the side reactions between the lithium supplement agent residue and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 Electrochemical impedance spectroscopy (EIS) of each single cell;

[0032] Figure 2 The cycle performance of each battery;

[0033] Figure 3 This is an electron microscope image of the lithium supplement agent of Example 1;

[0034] Figure 4 It is a schematic structural diagram of the lithium supplement of the present invention. DETAILED DESCRIPTION

[0035] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] In some optional embodiments

[0037] In a first aspect, the present invention provides a lithium supplement, including lithium-rich lithium ferrate;

[0038] The surface of the lithium-rich lithium ferrite is coated with carbon nanotubes and silicon carbide;

[0039] The mass percentage of the carbon nanotubes may be, for example, but not limited to, 0.01%, 0.05%, 0.1% or 0.5%;

[0040] The mass percentage of the silicon carbide may be, for example, but not limited to, 0.01%, 0.1% or 1%.

[0041] The lithium supplement provided by the present invention is obtained by coating carbon nanotubes and silicon carbide on the surface of lithium-rich lithium ferrite, wherein the carbon nanotubes can reduce the internal resistance of the battery, increase the liquid absorption rate of the battery positive electrode plate to the electrolyte, reduce the decomposition potential, reduce the side reaction of the battery cell, and improve the rate performance and cycle performance of the battery cell; the silicon carbide layer can reduce the crushing of the lithium supplement core and avoid the side reaction of the lithium supplement residue and the electrolyte.

[0042] In some optional embodiments, the chemical formula of the lithium-rich lithium iron oxide is: Li a Fe b O4;

[0043] Among them, 5.6≥a≥4.4, 1.2≥b≥0.8.

[0044] In a second aspect, the present invention provides a method for preparing the above-mentioned lithium supplement, comprising the following steps:

[0045] A lithium source and an iron source are mixed, and a precursor powder is obtained after heating treatment, and then the precursor powder is mixed with a carbon source and a silicon source to obtain a mixed powder, and then the mixed powder is sintered to prepare the lithium supplement agent;

[0046] The carbon source includes carbon nanotubes.

[0047] The preparation method is simple and convenient, and the prepared lithium supplement can effectively improve the rate performance and cycle performance of the battery cell.

[0048] In some optional embodiments, the lithium source includes but is not limited to lithium carbonate, lithium hydroxide or lithium oxide, or other lithium sources known to those skilled in the art.

[0049] In some optional embodiments, the iron source includes but is not limited to iron oxide, ferrosinite, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous citrate, ferrous sulfate or ferric hydroxide, or other iron sources known to those skilled in the art.

[0050] In some optional embodiments, the carbon source includes an inorganic carbon source and an organic carbon source in addition to carbon nanotubes;

[0051] The inorganic carbon source includes but is not limited to at least one of graphite, graphene, fullerene or carbon nanotube;

[0052] The organic carbon source includes, but is not limited to, at least one of glucose, sucrose, lignin urea, glycine or citric acid.

[0053] In some optional embodiments, the step of mixing the precursor powder with the carbon source and the silicon source to obtain a mixed powder comprises:

[0054] The precursor powder is mixed with a carbon source and a silicon source in a solvent, and a mixed powder is obtained after drying.

[0055] In some optional embodiments, the solvent includes but is not limited to ethanol, acetone, isopropanol, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0056] In some optional embodiments, the silicon source includes but is not limited to silicon powder and silicon dioxide.

[0057] In some optional embodiments, the sintering comprises: in an inert atmosphere, keeping the mixed powder at 400-600° C. for 4-8 hours, and then keeping it at 800-1000° C. for 8-12 hours.

[0058] In some optional embodiments, the sintering is: in an inert atmosphere, the mixed powder is heated to 400-600°C at a rate of 2-8°C / min, kept warm for 4-8 hours, cooled to room temperature and crushed, and then heated to 800-1000°C at a rate of 2-8°C / min, and kept warm for 8-12 hours.

[0059] In some optional embodiments, the sintering further includes a crushing process;

[0060] The crushing process includes crushing the sintered powder and passing it through 100-500 meshes to prepare a lithium supplement.

[0061] In a third aspect, the present invention provides a positive electrode sheet, wherein the slurry layer of the positive electrode sheet includes the above-mentioned lithium supplement agent.

[0062] The electrode has a high electrolyte absorption rate and low internal resistance.

[0063] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.

[0064] The lithium-ion battery is stable, is not prone to side reactions under high voltage conditions, and has good cycle performance.

[0065] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0066] Example 1

[0067] A lithium supplement, the electron microscope image of which is as follows Figure 3 As shown, the structural diagram is as follows Figure 4 As shown, it includes lithium-rich lithium ferrite and carbon nanotubes and silicon carbide coated on the surface of the lithium-rich lithium ferrite, wherein the lithium-rich lithium ferrite is: Li5FeO4, the mass proportion of carbon nanotubes is: 0.3%wt, and the mass proportion of silicon carbide is: 0.5%wt.

[0068] The preparation method is as follows:

[0069] Step 1, Li2CO3 and Li2O are mixed in a molar ratio of 1:1, and mixed by rotating at 200 rpm to obtain a composite lithium salt.

[0070] Step 2: Mix the composite lithium salt with Fe(NO3)3·9H2O (mix according to the molar ratio of lithium element to iron element of 5:1), and obtain a precursor powder after heating treatment.

[0071] Step 3, add a carbon and silicon-containing solution (a mixed solution of glucose, graphite, carbon nanotubes and silicon dioxide, by controlling the amount of precursor powder, carbon source and silicon source, so that the mass proportion of carbon nanotubes in the final product is: 0.3%wt, and the mass proportion of silicon carbide is: 0.5%wt) to the precursor powder and mix them for 2 hours to obtain a mixed solution of lithium salt, iron source and carbon-silicon source; after the mixed solution is dried, a mixed powder is obtained.

[0072] Step 4: The mixed powder is heated to 400-600°C at a rate of 2-8°C / min in nitrogen, kept warm for 4-8 hours, cooled to room temperature and crushed, and then heated to 800-1000°C at a rate of 2-8°C / min, kept warm for 8-12 hours, and continued to cool naturally to room temperature in an inert atmosphere in a furnace to obtain a carbon-coated lithium ferrite material.

[0073] Step 5, crushing: crush the above sintered material at a rotation speed of 300-1000 rpm for 0.5-2h, sieve 100-500 mesh, and obtain lithium-rich lithium iron oxide lithium supplement, namely CNTs&CSi@Li5FeO4.

[0074] Example 2

[0075] The difference from Example 1 is that in the lithium supplement, the lithium iron oxide rich in lithium is: Li 5.6 Fe 0.8 O4, the mass proportion of carbon nanotubes is: 0.01%wt, and the mass proportion of silicon carbide is: 0.01%wt.

[0076] Example 3

[0077] The difference from Example 1 is that in the lithium supplement, the lithium iron oxide rich in lithium is: Li 4.4 Fe 1.2 O4, the mass proportion of carbon nanotubes is: 0.5%wt, and the mass proportion of silicon carbide is: 1%wt.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that in the lithium supplement, the silicon carbide in the coating layer is replaced by an equal amount of carbon coating, and in the preparation method, silicon dioxide is replaced by a carbon source.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that in the lithium supplement, the coating layer does not include carbon nanotubes.

[0082] Test Example 1

[0083] The lithium supplement agents of the above examples and comparative examples were used to prepare positive electrode sheets and batteries, and further prepared into batteries.

[0084] Positive electrode sheet containing lithium supplement (experimental group): LiFePO4, CNTs & CSi @ Li5FeO4 of the embodiment or comparative example, carbon black, and PVDF are mixed in a ball mill at a mass ratio of 88:2:5:5, and N-methylpyrrolidone is used as a dispersion medium. The mixture is stirred and prepared into a positive electrode slurry, which is coated on the positive electrode collector, and then dried and rolled to obtain a positive electrode sheet.

[0085] Positive electrode sheet without lithium supplement agent (control group): LiFePO4, carbon black, and PVDF were mixed in a mass ratio of 90:5:5 and loaded into a ball mill, and N-methylpyrrolidone was used as a dispersion medium. The mixture was stirred and prepared into a positive electrode slurry, which was coated on the positive electrode collector and dried and rolled to obtain a positive electrode sheet.

[0086] Negative electrode sheet: Graphite, SBR, CMC and carbon black are mixed in a mass ratio of 96:1:1.5:1.5, and water is used as a dispersion medium. The mixture is stirred and prepared into a negative electrode slurry, which is then coated on the negative electrode current collector, and dried and rolled to obtain a negative electrode sheet.

[0087] The positive electrode sheets provided in the above-mentioned Examples 1-3 and Comparative Examples 1-2 and the positive electrode sheets of the control group were respectively combined with negative electrode sheets, separators, electrolytes, and aluminum-plastic films according to the same preparation method to prepare single-cell batteries, and the electrochemical impedance and room temperature cycle performance of each group of batteries were compared. The results are shown in FIG. Figure 1-Figure 2 shown.

[0088] from Figure 1 It can be seen that the EIS of Example 1 is the best, and the EIS of Examples 2-3 are close, all of which are greater than Comparative Examples 1-2.

[0089] from Figure 2It can be seen that the cycle retention rates of Examples 1 and 3 are close, and the cycle retention rate of Examples 1-3 is significantly better than that of Comparative Examples 1-2.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium supplement, characterized in that: Including lithium-rich lithium iron oxide; The surface of the lithium-rich lithium ferrite is coated with carbon nanotubes and silicon carbide; The mass proportion of the carbon nanotubes is 0.01%-0.5%; The mass proportion of the silicon carbide is 0.01%-1%.

2. The lithium supplement according to claim 1, characterized in that: The chemical formula of the lithium-rich iron oxide is: Li a Fe b O4; Among them, 5.6≥a≥4.4, 1.2≥b≥0.

8.

3. The method for preparing the lithium supplement according to claim 1 or 2, characterized in that: The following steps are involved: A lithium source and an iron source are mixed, and a precursor powder is obtained after heating treatment, and then the precursor powder is mixed with a carbon source and a silicon source to obtain a mixed powder, and then the mixed powder is sintered to prepare the lithium supplement agent; The carbon source includes carbon nanotubes.

4. The preparation method according to claim 3, characterized in that: The lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium oxide.

5. The preparation method according to claim 3, characterized in that: The iron source includes at least one of ferric oxide, ferroferric oxide, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous citrate, ferrous sulfate or ferric hydroxide.

6. The preparation method according to claim 3, characterized in that: The carbon source also includes inorganic carbon source and organic carbon source; The inorganic carbon source includes at least one of graphite, graphene, fullerene or carbon nanotube; The organic carbon source includes at least one of glucose, sucrose, lignin urea, glycine or citric acid.

7. The preparation method according to claim 3, characterized in that: The silicon source includes silicon powder and silicon dioxide.

8. The preparation method according to claim 3, characterized in that: The sintering comprises: in an inert atmosphere, keeping the mixed powder at 400-600° C. for 4-8 hours, and then keeping it at 800-1000° C. for 8-12 hours.

9. A positive electrode sheet, characterized in that: The slurry layer of the positive electrode sheet includes the lithium supplement agent according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Lithium supplementing cathode material containing Co-doped lithium ferrate and preparation thereof, and application of lithium supplementing cathode material containing Co-doped lithium ferrate

    CN110518298A

  • Anode lithium supplement agent, anode plate and method for preparing anode lithium supplement agent

    CN114050258A